Human appearance: What does not appear in what appears - Curkpatrick, Stephen (Sekolah Tinggi Teologi Sangkakala & Sekolah Tinggi Jemaat Kristus Indonesia, 2024)
The human person is a quintessential example of appearance necessitating and moderated by what does not appear. The question of what is real concerns non-appearing dynamics of what makes any appearance possible. Concerning human life, what then is the unseen impetus of corporeal life and activity? This is a focus on the animating and motivating impetus of human life that is customarily equated with soul, psyche or the unique I, which actively relates to others, yet remains inaccessible to their gaze, apart from self-representation by words, gestures and actions of a body. Appearance is here dependent on a profound non-appearance without which, there are no human appearances or indeed, appearances of anything to human consciousness. Engaging selected writings of Leibniz, this article gives particular focus to the concept of soul in relation to impetus, appetition and purpose in human appearance as an expressive body.